The Effect of The Implementation of Total Quality Management on Student Learning Achievement at SMA Islam Al-Azhar 10 Pontianak - Raziki Waldan (AT-TURATS, 2020)
Efforts to improve the quality of education through a school empowerment approach in managing their institutions, the Ministry of National Education has been doing it for a long time. In the era of regional autonomy, which is implicitly stated in Law Number 22 of 1999, and which was effectively enforced from January 1, 2001, school empowerment emerged through School-Based Management (MBS). With the existence of regional autonomy, schools are freer to develop through initiative, creativity, innovation, and subsequently competitive or able to compete with other schools specifically to improve the quality of these schools and in general to improve the quality of national education. In improving the quality of education, SMA AL-Azhar 10 Pontianak applies TQM, which is a management model that focuses on people that aims to continuously improve customer satisfaction at real costs which are continuously decreasing. And TQM is an alternative that must be applied in educational institutions. With this management, it is expected that school effectiveness will be realized perfectly. The research in this article was conducted to examine the effect of TQM in improving student achievement at SMA AL-Azhar 10 Pontianak to improve the quality of education and achievement in the institution. This type of research uses quantitative research. And data collection is done by interview, observation, and questionnaire methods. The analysis used is quantitative statistical data analysis using the product-moment formula. From the results of the analysis, it was proven that the TQM carried out at SMA AL-Azhar 10 Pontianak was classified as good, meaning that it was running well. And learning achievement at SMA AL-Azhar 10 Pontianak has increased with evidence of increasing graduates and several competitions according to research results and classified as more than adequate category. While the influence of TQM in improving student achievement at SMA AL-Azhar 10 Pontianak has a very strong and very high influence with a product-moment interpretation value of 1.03. One of our suggestions for schools is for all teachers to be even more creative in using and utilizing TQM to develop schools so that students are more enthusiastic about achieving the highest achievement.